KRITIK AL-QUR`AN DALAM KONTRA NARASI PENDUSTA AGAMA STUDI TAFSIR SURAH AL-MA’UN AYAT 1-3 - Aan Handriyani (Jurnal Da'wah: Risalah Merintis, Da'wah Melanjutkan, 2025)
Makki Surahs reflect the atmosphere of the early Da’wah of the Prophet Muhammad (SAW), which was marked by the opposition and narratives of arrogance from the Quraysh leaders. Many verses of the Quran, including Surah Al-Ma’un (classified as Makki by the majority of scholars), function to critique and refute these narratives of denial. The objective of this study is to identify and analyze the Quran`s model of critique and counter-narrative against religious deniers through an in-depth tafsir (exegesis) study of Surah Al-Ma’un verses 1-3. Methodology: This qualitative research employs a combined approach, utilizing the Tafsir Maudhu'i (Thematic Exegesis) method and the Tafsir Tahlili (Analytical Exegesis) method, specifically focusing on verses 1-3 of Surah Al-Ma’un. Findings: The research results show that Surah Al-Ma’un verses 1-3 utilizes two main uslub (rhetorical styles): Uslub Istifhâm (The Rhetorical Question) is used to present a critique in the form of extreme astonishment (mubālaghah fī at-ta’ajjub) and to evoke interest (tasywîq). Uslub Khabary (The Declarative Statement) asserts that the poor social behavior of the disbelievers originates from their fundamental denial of the Day of Recompense. Through this uslub al-khabar, Surah Al-Ma’un verses 1-3 performs narrative reframing: the narratives of Quraysh arrogance are completely dismantled and replaced with a narrative emphasizing the severe consequences of denying the Day of Recompense, which manifests in reprehensible social conduct, not only according to Shari'ah (Islamic law) but also according to human dignity (muru'ah) and ethics.